2018
DOI: 10.3390/md16010029
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Extraction Conditions and Characterization of Pepsin-Solubilised Collagen from Skin of Giant Croaker (Nibea japonica)

Abstract: In the present study, response surface methodology was performed to investigate the effects of extraction parameters on pepsin-solubilised collagen (PSC) from the skin of the giant croaker Nibea japonica. The optimum extraction conditions of PSC were as follows: concentration of pepsin was 1389 U/g, solid-liquid ratio was 1:57 and hydrolysis time was 8.67 h. Under these conditions, the extraction yield of PSC was up to 84.85%, which is well agreement with the predict value of 85.03%. The PSC from Nibea japonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 34 publications
7
45
0
Order By: Relevance
“…These outcomes were certainly surprising since the expected pattern for the hydrolysis time would be an asymptotic curve (e.g., sigmoid or hyperbolic) rather than the present concave surface observed. No clear assumption could be set to explain this behavior, but a similar parabolic trend for the time of hydrolysis was found in the extraction of antioxidants from surplus tomato crop assisted by microwave [ 27 ], the solubilization of collagen from croaker skin by pepsin hydrolysis [ 28 ], enzyme hydrolysis of fish processing waste [ 29 ] and the production of fish protein hydrolysates [ 30 ]. For the NaOH-EtOH treatment, the surfaces were convex domes, with a clear maximum response, in agreement with the results obtained in the precipitation of CS from other cartilaginous fish species [ 26 , 31 ].…”
Section: Resultsmentioning
confidence: 98%
“…These outcomes were certainly surprising since the expected pattern for the hydrolysis time would be an asymptotic curve (e.g., sigmoid or hyperbolic) rather than the present concave surface observed. No clear assumption could be set to explain this behavior, but a similar parabolic trend for the time of hydrolysis was found in the extraction of antioxidants from surplus tomato crop assisted by microwave [ 27 ], the solubilization of collagen from croaker skin by pepsin hydrolysis [ 28 ], enzyme hydrolysis of fish processing waste [ 29 ] and the production of fish protein hydrolysates [ 30 ]. For the NaOH-EtOH treatment, the surfaces were convex domes, with a clear maximum response, in agreement with the results obtained in the precipitation of CS from other cartilaginous fish species [ 26 , 31 ].…”
Section: Resultsmentioning
confidence: 98%
“…The peaks contained five main amide bonds, including amide A, B, I, II, and III ( Figure 4 ). The free N-H stretching vibration occurs at wave number ranging from 3400 cm −1 to 3440 cm −1 , with a shift near 3300 cm −1 because of the presence of hydrogen bonds [ 19 ]. The amide A band, which is associated with N-H stretching frequency, occurred at 3304.82 and 3305.90 cm −1 for ASC and PSC, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The giant croaker ( Nibea japonica ) is now cultured as a promising species for marine aquaculture in East Asia [ 18 , 19 ]. The growth rate of this fish is high (it can reach up to 0.4–0.5 kg in one year) and its price is approximately 6.2 dollars/kg on the Chinese market.…”
Section: Introductionmentioning
confidence: 99%
“…However, Ran and Wang state that the ultrasound extraction method could break the hydrogen bonds in the collagen chains, causing denaturation of the protein and the enzyme used for its isolation [40]. In reference to Yu et al, various enzymes were used for the extraction of collagen, finding that the activity of papain was inhibited by structural changes in its activity, while pepsin did not change [41]. In addition, they reported that the application of ultrasound for long periods of time causes a rise in temperature leading to the denaturation of collagen.…”
Section: Methods Of Extraction Of Collagen Of Aquatic Originmentioning
confidence: 99%